Analysis of Leadership Style and Work Motivation on Employee Work Morale at the Social Affairs Office of Sibolga City - Tika Irawana Hutagalung; Nelly Azwarni Sinaga; Muhammad Iqbal Batubara (Journal of Economics, Management and Accounting (JEMA), 2025)
This study aims to analyze the influence of leadership style and work motivation on employees’ work morale at the Social Service Office of Sibolga City. The research employed a quantitative approach using multiple linear regression analysis. The population consisted of 42 employees, all of whom were selected as the research sample (total sampling). Data were collected through the distribution of questionnaires and analyzed using SPSS software. The results indicate that leadership style has a positive and significant effect on employees’ work morale, with a significance value of 0.013 (< 0.05). Work motivation also has a positive and significant effect on work morale, with a significance value of 0.026 (< 0.05). Simultaneously, leadership style and work motivation have a positive and significant effect on employees’ work morale, with a coefficient of determination (R²) of 0.471, indicating that 47.1% of the variation in work morale can be explained by these two variables, while the remaining percentage is influenced by other factors outside the scope of this study.